Breast Cancer Diagnosis and Management in an Area of Protracted Conflict: A Case Series from Northwest Syria - Mohamed Hamze; Jude Alawa; Fares Alahdab; Alaa Al-Shemali; Ahmed Najeb Alhussein; Nour Muhammed Ali Arab; Bayan Galal; Jamil Debel; Ayham Jemo; Molham khalil; Anees Chagpar; Bassel Atassi; et al. (Avicenna Journal of Medicine)
Background Breast cancer remains a significant public health challenge in conflict-affected regions. This study aims to investigate the impact of armed conflict on the burden of breast cancer in female patients in northwest Syria, focusing on clinical presentations, management, diagnosis, access to care, and treatment outcomes.